High prevalence of D/G group acrocentric RPL chromosome polymorphisms in 1400 recurrent pregnancy losses patients, an evaluation of genetic factor and reassessing CPMs in 21st century as normal variants? - Fauzdar, Ashish; Dixit, Vikas; Mavi, Ritu; Khan, Tanzila; Arya, Rahul; Sharma, Neeraj Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The current burden for recurrent pregnancy losses in India is quite high and is around 7.4% and majority of them with no definitive cause for pregnancy loss even after complete RPL workup. The objective of the study was to investigate the prevalence and possible association of chromosome polymorphisms with recurrent pregnancy loss patients. Methods: A single centre case-control retrospective study on RPL patients undergoing conventional cytogenetics culture techniques to rule out chromosome abnormalities. Results: The prevalence of chromosome polymorphism in the study was 33.7% (471/1400) high in comparison to previous studies. The acro ps+/- polymorphisms involving D/G group of chromosomes was significantly higher in the study group observed in 23.5% (330/1400) patients and 15.8% (58/366) in the control group p <0.005. The prevalence of 22ps+ subtype polymorphism was significantly higher in the patient groups with the odd ratio OR (95% CI)- 2.35 (1.245-4.434). Conclusions: This study substantiates the very high prevalence of CPMs and therefore should be interpreted cautiously till further strong evidence are available, until then patient should be counselled on case-to case basis. In future CPMs may play a crucial role in prognosis and management in unexplained RPL group with no other definitive cause identified after RPL workup as per recommendations from international and national guidelines.